Effect of stress on contextual pain sensitivity in the preoperative period- A proof of concept study - Shibani Padhy; Ruhi Fatima; Shubhranshu Jena; Akhya Kumar Kar; Padmaja Durga; Vishal Kumar Neeradi (Journal of Anaesthesiology Clinical Pharmacology, 2023)
Background and Aims: The importance of non-noxious contextual inputs in the interplay of pain with neurophysiologic and behavioral factors is gaining recognition. Stress of impending surgery can act as a negative context, leading to a decrease in pain threshold in patients. This study was conducted to assess the influence of stress conferred by the imminent and other contextual inputs such as anxiety, socioeconomic status, prior painful experience, and the effect of gender on modulation of pain perception in patients undergoing elective surgery. Material and Methods: In total, 120 patients aged between 18 and 60 years of either gender posted for elective gastrointestinal surgery under general anesthesia were recruited. Data were collected on preoperative anxiety level, socioeconomic status, education, and any prior painful experience. A pressure algometer was used to measure the pressure pain thresholds and pain tolerance on the day before surgery and on the morning of surgery in the preoperative suite. Results: There was a statistically significant decrease in both pain threshold (P < 0.0001) and pain tolerance in the immediate preoperative period in comparison to the baseline readings taken the day before surgery (P = 0.048). The magnitude of change in pain scalars was greater in females (P < 0.001), those with a high anxiety score, and a history of severe painful experience in the past. Conclusion: Preoperative surgical stress lowers the pain threshold and pain tolerance. Contextual modulation of pain by factors such as anxiety and memory of prior painful experience, especially in the female gender, could influence postoperative patient outcomes and warrants further research.